Morphology‐Engineered Highly Active and Stable Ru/TiO2 Catalysts for Selective CO Methanation - Chen, Shilong; Abdel‐Mageed, Ali M.; Li, Dan; Bansmann, Joachim; Cisneros, Sebastian; Biskupek, Johannes; Huang, Weixin; Behm, R. Jürgen (Angewandte Chemie International Edition, 2019)
Ru/TiO2 catalysts exhibit an exceptionally high activity in the selective methanation of CO in CO2‐ and H2‐rich reformates, but suffer from continuous deactivation during reaction. This limitation can be overcome through the fabrication of highly active and non‐deactivating Ru/TiO2 catalysts by engineering the morphology of the TiO2 support. Using anatase TiO2 nanocrystals with mainly {001}, {100}, or {101} facets exposed, we show that after an initial activation period Ru/TiO2‐{100} and Ru/TiO2‐{101} are very stable, while Ru/TiO2‐{001} deactivates continuously. Employing different operando/in situ spectroscopies and ex situ characterizations, we show that differences in the catalytic stability are related to differences in the metal–support interactions (MSIs). The stronger MSIs on the defect‐rich TiO2‐{100} and TiO2‐{101} supports stabilize flat Ru nanoparticles, while on TiO2‐{001} hemispherical particles develop. The former MSIs also lead to electronic modifications of Ru surface atoms, reflected by the stronger bonding of adsorbed CO on those catalysts than on Ru/TiO2‐{001}. Keeping it flat: Morphology‐engineered TiO2‐{100} and TiO2‐{101} nanocrystal supports can stabilize flat Ru nanoparticles, resulting in a very stable activity of the Ru/TiO2 catalysts for the selective CO methanation. Weaker metal–support interactions on the TiO2‐{001} nanocrystals result in a shape change of the Ru nanoparticles, from flat to hemispherical, together with continuous deactivation.